Anti-wear and anti-attrition compound lubricating oil as well as preparation method and application thereof

By using composite lubricating oil with modified layered molybdenum oxide and sublimated sulfur in the lubricating oil, the problem of insufficient protection ability of existing extreme pressure anti-wear agents under high load conditions is solved, and the excellent anti-wear and wear reduction effect and extreme pressure performance of lubricating oil are achieved.

CN119505980AActive Publication Date: 2025-02-25JINING XIAOSONG LUBRICATING OIL XIAOSHOU CO LTD

Patent Information

Application Number
CN202411664459.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing extreme pressure antiwear agents have limited protection capabilities under high load conditions and cannot significantly improve the extreme pressure performance of lubricating oil, resulting in frequent equipment wear and failure.

Method used

An anti-wear and wear-reducing composite lubricating oil is adopted, which consists of base oil, modified layered molybdenum oxide, sublimated sulfur, preservatives, antioxidants, viscosity index improvers and dispersants. Through specific preparation methods and combined proportions, an extreme pressure anti-wear and wear-reducing effect and extreme pressure performance is formed.

Benefits of technology

Significantly reduce the diameter of the wear spot, improve the maximum no-block load, enhance the performance of lubricant under high load conditions, and significantly improve the anti-wear and wear reduction effect and extreme pressure performance of lubricant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144254870000091
    Figure BDA0005144254870000091
Patent Text Reader

Abstract

The invention relates to the technical field of lubricating oil, in particular to anti-wear and anti-attrition composite lubricating oil and a preparation method and application thereof. The anti-wear and anti-attrition composite lubricating oil is prepared from the following raw materials: base oil, an anti-wear reagent at extreme pressure, a preservative, an antioxidant, a viscosity index improver and a dispersing agent, the extreme pressure anti-wear agent is obtained by modifying layered molybdenum oxide with metal micelles formed by dodecylamine and wet and then carrying out hydrothermal treatment and vulcanization. The prepared anti-wear and anti-attrition composite lubricating oil has excellent anti-wear and anti-attrition effects and extreme pressure properties, is suitable for the lubrication requirements under high load and harsh conditions, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating oils, and in particular to an anti-wear and friction-reducing composite lubricating oil and a preparation method and application thereof. Background Art

[0002] Lubricants play a vital role in modern industrial and mechanical applications. As mechanical equipment develops towards high load, high speed and high precision, the performance requirements for lubricants are getting higher and higher. Traditional lubricants are prone to failure under extreme conditions, resulting in increased equipment wear, increased energy consumption, and even equipment failure. Therefore, the development of lubricants with excellent anti-wear and extreme pressure properties has become a hot topic in current research.

[0003] Extreme pressure anti-wear agents are key additives in lubricants that provide additional protection under high load conditions. They form a protective film on the friction surface through chemical reactions, enhancing the load-bearing capacity and stability of the oil film. However, existing extreme pressure anti-wear agents have limited protection under high load conditions and cannot significantly improve the extreme pressure performance of lubricants. This results in suboptimal lubricant performance in high-load applications, and equipment is prone to wear and failure. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide an anti-wear and friction-reducing composite lubricant and a preparation method and application thereof, so as to meet the lubrication needs under high load and severe conditions.

[0005] Based on the above purpose, the present invention provides an anti-wear and friction-reducing composite lubricating oil, which is prepared from the following raw materials by weight: 60-80 parts of base oil, 2-4 parts of extreme pressure anti-wear agent, 0.5-1 part of preservative, 1-3 parts of antioxidant, 1-3 parts of viscosity index improver and 1-2 parts of dispersant;

[0006] Furthermore, the preparation method of the extreme pressure anti-wear agent is as follows:

[0007] (1) adding dodecylamine to a mixed solution of deionized water and ethanol, stirring for 10-30 minutes, then adding cerium nitrate hexahydrate and layered molybdenum oxide, continuing to stir for 20-40 minutes, then hydrothermally reacting at 230-250° C. for 20-28 hours, washing, and drying to obtain a modified layered molybdenum oxide;

[0008] (2) The modified layered molybdenum oxide and sublimed sulfur are mixed and ball-milled for 1-3 hours to obtain a mixture, which is heated from room temperature to 750-850° C. at a rate of 1-10° C. / min under an argon atmosphere, calcined for 2-4 hours, cooled, and ground to obtain an extreme pressure anti-wear agent.

[0009] Preferably, in step (1), the weight ratio of dodecylamine, deionized water, ethanol, cerium nitrate hexahydrate and layered molybdenum oxide is 9-24:400-600:70-130:2-6:5-15.

[0010] Preferably, in step (2), the weight ratio of the modified layered molybdenum oxide to the sublimated sulfur is 1:1.5-3.

[0011] Preferably, the base oil is a mixture of polyalphaolefin PAO4 and polyalphaolefin PAO6 in a weight ratio of 5:1-3.

[0012] Preferably, the preservative is benzotriazole.

[0013] Preferably, the antioxidant is a phenolic antioxidant.

[0014] Preferably, the viscosity index improver is polymethacrylate or ethylene propylene copolymer.

[0015] Preferably, the dispersant is polyisobutylene succinimide.

[0016] Preferably, the preparation method of the layered molybdenum oxide is as follows: sodium molybdate dihydrate and sodium chloride are added to deionized water, stirred for 20-40 minutes, then adjusted to pH 2-3 with aqueous hydrochloric acid solution, hydrothermally reacted at 170-190° C. for 20-28 hours, naturally cooled to room temperature, washed, and dried to obtain layered molybdenum oxide.

[0017] Preferably, the weight ratio of sodium molybdate dihydrate, sodium chloride and deionized water is 9-27:4-15:300-700.

[0018] Preferably, the concentration of the aqueous hydrochloric acid solution is 1-5 mol / L.

[0019] Furthermore, the present invention also provides a method for preparing an anti-wear and friction-reducing composite lubricant, comprising the following steps: heating the base oil to 150°C, then adding an extreme pressure anti-wear agent, a preservative, an antioxidant, a viscosity index improver and a dispersant, stirring for 20-40 minutes, cooling, and obtaining the anti-wear and friction-reducing composite lubricant.

[0020] Furthermore, the present invention also provides an application of an anti-wear and friction-reducing composite lubricant, which can be used for lubrication under high load and severe conditions.

[0021] Beneficial effects of the present invention:

[0022] The present invention significantly reduces the wear spot diameter from 472.4 μm to 192.6 μm by adding an extreme pressure anti-wear agent, showing excellent anti-wear and wear reduction effects. At the same time, the maximum no-seizure load reaches 720N, which is 45.5% higher than that of lubricating oil without adding an extreme pressure anti-wear agent, significantly enhancing the performance of the lubricating oil under high load conditions.

[0023] Compared with the traditional layered molybdenum oxide, the extreme pressure anti-wear agent provided by the present invention further improves the anti-wear and friction-reducing effect and extreme pressure performance of the lubricating oil. In addition, the sulfurization treatment of sublimated sulfur plays an important role in improving the anti-wear and friction-reducing effect of the lubricating oil, especially in improving the extreme pressure performance, showing the importance of sulfurization treatment in optimizing the performance of lubricating oil.

[0024] The lamellar molybdenum oxide modified by dodecylamine and cerium used in the present invention significantly improves the anti-wear and friction-reducing effect and extreme pressure performance of lubricating oil. The mechanism is that the metal ion micelles formed by dodecylamine and cerium can be intercalated and adsorbed on the inner and outer surfaces of the lamellar molybdenum oxide, and after hydrothermal treatment, cerium-doped carbon particles are formed, which enhances the adsorption capacity and interlayer slip of the lamellar molybdenum oxide on the friction surface.

[0025] In summary, the anti-wear and friction-reducing composite lubricating oil of the present invention has excellent anti-wear and friction-reducing effects and extreme pressure performance, is suitable for lubrication needs under high loads and severe conditions, and has broad application prospects. DETAILED DESCRIPTION

[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0027] Embodiment 1:

[0028] (1) 9 g of sodium molybdate dihydrate and 4 g of sodium chloride were added to 300 g of deionized water, stirred for 20 min, then adjusted to pH 2.1 with 5 mol / L hydrochloric acid, transferred to a reactor, subjected to hydrothermal reaction at 170 ° C for 20 h, cooled naturally to room temperature, washed with deionized water and ethanol for 3 times, and finally dried at 80 ° C for 12 h to obtain layered molybdenum oxide;

[0029] (2) adding 9 g of dodecylamine to a mixed solution of 400 g of deionized water and 70 g of ethanol, stirring for 10 min, then adding 2 g of cerium nitrate hexahydrate and 5 g of layered molybdenum oxide, stirring for 20 min, then transferring to a hydrothermal reactor, hydrothermally reacting at 230 ° C for 20 h, washing with deionized water and ethanol for 3 times respectively, and finally drying at 80 ° C for 12 h to obtain a modified layered molybdenum oxide;

[0030] (3) 10 g of modified layered molybdenum oxide and 15 g of sublimed sulfur were mixed and ball-milled for 1 h at a ball mill speed of 20 rpm to obtain a mixture, which was then transferred to a tube furnace and heated from room temperature to 750 ° C at a rate of 1 ° C / min under an argon atmosphere, calcined for 2 h, cooled, and ground to obtain an extreme pressure anti-wear agent;

[0031] (4) 50 g of polyalphaolefin PAO4 and 10 g of polyalphaolefin PAO6 were heated to 150° C., and then 2 g of extreme pressure anti-wear agent, 0.5 g of benzotriazole, 1 g of antioxidant 264, 1 g of viscosity index improver HSD-TZ0009 and 1 g of dispersant T154A were added, stirred for 20 min, and cooled to obtain an anti-wear and friction-reducing composite lubricant.

[0032] Embodiment 2:

[0033] (1) 18.15 g of sodium molybdate dihydrate and 9 g of sodium chloride were added to 500 g of deionized water, stirred for 30 min, then adjusted to pH 2.5 with 5 mol / L hydrochloric acid, transferred to a reactor, subjected to hydrothermal reaction at 180 ° C for 24 h, cooled naturally to room temperature, washed with deionized water and ethanol for 3 times, and finally dried at 80 ° C for 12 h to obtain layered molybdenum oxide;

[0034] (2) adding 18.5 g of dodecylamine to a mixed solution of 500 g of deionized water and 100 g of ethanol, stirring for 20 min, then adding 4.3 g of cerium nitrate hexahydrate and 10 g of layered molybdenum oxide, stirring for 30 min, then transferring to a hydrothermal reactor, hydrothermally reacting at 240 ° C for 24 h, washing with deionized water and ethanol for 3 times respectively, and finally drying at 80 ° C for 12 h to obtain a modified layered molybdenum oxide;

[0035] (3) 10 g of modified layered molybdenum oxide and 20 g of sublimated sulfur were mixed and ball-milled for 2 h at a ball mill speed of 20 rpm to obtain a mixture, which was then transferred to a tube furnace and heated from room temperature to 800 ° C at a rate of 5 ° C / min under an argon atmosphere, calcined for 3 h, cooled, and ground to obtain an extreme pressure anti-wear agent;

[0036] (4) 50 g of polyalphaolefin PAO4 and 20 g of polyalphaolefin PAO6 were heated to 150° C., and then 3 g of extreme pressure anti-wear agent, 0.8 g of benzotriazole, 2 g of antioxidant 264, 2 g of viscosity index improver HSD-TZ0009 and 1.5 g of dispersant T154A were added, stirred for 30 min, and cooled to obtain an anti-wear and friction-reducing composite lubricant.

[0037] Embodiment 3:

[0038] (1) 27 g of sodium molybdate dihydrate and 15 g of sodium chloride were added to 700 g of deionized water, stirred for 40 min, then adjusted to pH 3 with 1 mol / L hydrochloric acid, transferred to a reactor, subjected to hydrothermal reaction at 190 ° C for 28 h, cooled naturally to room temperature, washed with deionized water and ethanol for 3 times, and finally dried at 80 ° C for 12 h to obtain layered molybdenum oxide;

[0039] (2) adding 24 g of dodecylamine to a mixed solution of 600 g of deionized water and 130 g of ethanol, stirring for 30 min, then adding 6 g of cerium nitrate hexahydrate and 15 g of layered molybdenum oxide, stirring for 40 min, then transferring to a hydrothermal reactor, hydrothermally reacting at 250 ° C for 28 h, washing with deionized water and ethanol for 3 times respectively, and finally drying at 80 ° C for 12 h to obtain a modified layered molybdenum oxide;

[0040] (3) 10 g of modified layered molybdenum oxide and 30 g of sublimated sulfur were mixed and ball-milled for 3 h at a ball mill speed of 20 rpm to obtain a mixture, which was then transferred to a tube furnace and heated from room temperature to 850 ° C at a rate of 10 ° C / min under an argon atmosphere, calcined for 4 h, cooled, and ground to obtain an extreme pressure anti-wear agent;

[0041] (4) 50 g of polyalphaolefin PAO4 and 30 g of polyalphaolefin PAO6 were heated to 150° C., and then 4 g of extreme pressure anti-wear agent, 1 g of benzotriazole, 3 g of antioxidant 264, 3 g of viscosity index improver HSD-TZ0009 and 2 g of dispersant T154A were added, stirred for 40 min, and cooled to obtain an anti-wear and friction-reducing composite lubricant.

[0042] Comparative Example 1:

[0043] The difference between Comparative Example 1 and Example 2 is that the extreme pressure anti-wear agent in step (4) is replaced by layered molybdenum oxide;

[0044] The specific steps are as follows:

[0045] (1) 18.15 g of sodium molybdate dihydrate and 9 g of sodium chloride were added to 500 g of deionized water, stirred for 30 min, then adjusted to pH 2.5 with 5 mol / L hydrochloric acid, transferred to a reactor, subjected to hydrothermal reaction at 180 ° C for 24 h, cooled naturally to room temperature, washed with deionized water and ethanol for 3 times, and finally dried at 80 ° C for 12 h to obtain layered molybdenum oxide;

[0046] (2) 50 g of polyalphaolefin PAO4 and 20 g of polyalphaolefin PAO6 were heated to 150° C., and then 3 g of layered molybdenum oxide, 0.8 g of benzotriazole, 2 g of antioxidant 264, 2 g of viscosity index improver HSD-TZ0009 and 1.5 g of dispersant T154A were added, stirred for 30 min, and cooled to obtain lubricating oil.

[0047] Comparative Example 2:

[0048] The difference between Comparative Example 2 and Example 2 is that the extreme pressure anti-wear agent in step (4) is replaced by modified layered molybdenum oxide;

[0049] The specific steps are as follows:

[0050] (1) 18.15 g of sodium molybdate dihydrate and 9 g of sodium chloride were added to 500 g of deionized water, stirred for 30 min, then adjusted to pH 2.5 with 5 mol / L hydrochloric acid, transferred to a reactor, subjected to hydrothermal reaction at 180 ° C for 24 h, cooled naturally to room temperature, washed with deionized water and ethanol for 3 times, and finally dried at 80 ° C for 12 h to obtain layered molybdenum oxide;

[0051] (2) adding 18.5 g of dodecylamine to a mixed solution of 500 g of deionized water and 100 g of ethanol, stirring for 20 min, then adding 4.3 g of cerium nitrate hexahydrate and 10 g of layered molybdenum oxide, stirring for 30 min, then transferring to a hydrothermal reactor, hydrothermally reacting at 240 ° C for 24 h, washing with deionized water and ethanol for 3 times respectively, and finally drying at 80 ° C for 12 h to obtain a modified layered molybdenum oxide;

[0052] (3) 50 g of polyalphaolefin PAO4 and 20 g of polyalphaolefin PAO6 were heated to 150° C., and then 3 g of modified layered molybdenum oxide, 0.8 g of benzotriazole, 2 g of antioxidant 264, 2 g of viscosity index improver HSD-TZ0009 and 1.5 g of dispersant T154A were added, stirred for 30 min, cooled, and lubricating oil was obtained.

[0053] Comparative Example 3:

[0054] The difference between Comparative Example 3 and Example 2 is that: cerium nitrate hexahydrate is not added in step (2);

[0055] The specific steps are as follows:

[0056] (1) 18.15 g of sodium molybdate dihydrate and 9 g of sodium chloride were added to 500 g of deionized water, stirred for 30 min, then adjusted to pH 2.5 with 5 mol / L hydrochloric acid, transferred to a reactor, subjected to hydrothermal reaction at 180 ° C for 24 h, cooled naturally to room temperature, washed with deionized water and ethanol for 3 times, and finally dried at 80 ° C for 12 h to obtain layered molybdenum oxide;

[0057] (2) adding 18.5 g of dodecylamine to a mixed solution of 500 g of deionized water and 100 g of ethanol, stirring for 20 min, then adding 10 g of layered molybdenum oxide, continuing to stir for 30 min, then transferring to a hydrothermal reactor, hydrothermally reacting at 240 ° C for 24 h, washing with deionized water and ethanol for 3 times respectively, and finally drying at 80 ° C for 12 h to obtain a modified layered molybdenum oxide;

[0058] (3) 10 g of modified layered molybdenum oxide and 20 g of sublimated sulfur were mixed and ball-milled for 2 h at a ball mill speed of 20 rpm to obtain a mixture, which was then transferred to a tube furnace and heated from room temperature to 800 ° C at a rate of 5 ° C / min under an argon atmosphere, calcined for 3 h, cooled, and ground to obtain an extreme pressure anti-wear agent;

[0059] (4) 50 g of polyalphaolefin PAO4 and 20 g of polyalphaolefin PAO6 were heated to 150° C., and then 3 g of extreme pressure anti-wear agent, 0.8 g of benzotriazole, 2 g of antioxidant 264, 2 g of viscosity index improver HSD-TZ0009 and 1.5 g of dispersant T154A were added, stirred for 30 min, cooled, and lubricating oil was obtained.

[0060] Comparative Example 4:

[0061] The difference between Comparative Example 4 and Example 2 is that: dodecylamine is not added in step (2);

[0062] The specific steps are as follows:

[0063] (1) 18.15 g of sodium molybdate dihydrate and 9 g of sodium chloride were added to 500 g of deionized water, stirred for 30 min, then adjusted to pH 2.5 with 5 mol / L hydrochloric acid, transferred to a reactor, subjected to hydrothermal reaction at 180 ° C for 24 h, cooled naturally to room temperature, washed with deionized water and ethanol for 3 times, and finally dried at 80 ° C for 12 h to obtain layered molybdenum oxide;

[0064] (2) adding 4.3 g of cerium nitrate hexahydrate and 10 g of layered molybdenum oxide to a mixed solution of 500 g of deionized water and 100 g of ethanol, stirring for 30 min, then transferring to a hydrothermal reactor, hydrothermally reacting at 240 ° C for 24 h, washing with deionized water and ethanol for 3 times, respectively, and finally drying at 80 ° C for 12 h to obtain a modified layered molybdenum oxide;

[0065] (3) 10 g of modified layered molybdenum oxide and 20 g of sublimated sulfur were mixed and ball-milled for 2 h at a ball mill speed of 20 rpm to obtain a mixture, which was then transferred to a tube furnace and heated from room temperature to 800 ° C at a rate of 5 ° C / min under an argon atmosphere, calcined for 3 h, cooled, and ground to obtain an extreme pressure anti-wear agent;

[0066] (4) 50 g of polyalphaolefin PAO4 and 20 g of polyalphaolefin PAO6 were heated to 150° C., and then 3 g of extreme pressure anti-wear agent, 0.8 g of benzotriazole, 2 g of antioxidant 264, 2 g of viscosity index improver HSD-TZ0009 and 1.5 g of dispersant T154A were added, stirred for 30 min, cooled, and lubricating oil was obtained.

[0067] Comparative Example 5:

[0068] The difference between Comparative Example 5 and Example 2 is that no extreme pressure anti-wear agent is added in step (4);

[0069] The specific steps are as follows:

[0070] 50g of polyalphaolefin PAO4 and 20g of polyalphaolefin PAO6 were heated to 150°C, and then 0.8g of benzotriazole, 2g of antioxidant 264, 2g of viscosity index improver HSD-TZ0009 and 1.5g of dispersant T154A were added, stirred for 30 minutes, cooled, and lubricating oil was obtained.

[0071] Performance Test:

[0072] Anti-wear performance: A four-ball wear tester was used to evaluate the anti-wear performance of the composite oil according to the standard ASTM D4172-21. The test steel ball had a diameter of 12.7 mm and a Rockwell hardness of 64. Three 12.7 mm steel balls were fixed together, the steel balls were immersed in lubricating oil, and the top ball was squeezed into the cavity formed by the three clamping balls at 147 N to make three-point contact. After the temperature was set to 75 ° C, the top ball was rotated at a speed of 1200 r / min for 60 minutes, and the wear spot diameters on the three lower steel balls were measured. The results are shown in Table 1.

[0073] Extreme pressure performance: The extreme pressure performance of the composite oil was tested using the standard ASTM D2783-21. The speed was 1760r / min, the temperature of the machine and the test lubricant oil was increased from 18°C ​​to 35°C, and then the test was carried out under increasing load until welding occurred. The load at which welding occurred was the maximum no-seizure load. The results are shown in Table 1.

[0074] Table 1 Performance test results

[0075]

[0076] Data Analysis:

[0077] It can be seen from the data of Examples 1-3 and Comparative Example 5 in Table 1 that the anti-wear and friction-reducing composite lubricating oil prepared by the present invention has excellent anti-wear and friction-reducing effects and extreme pressure performance. Compared with the lubricating oil without adding extreme pressure anti-wear agent, the wear spot diameter is reduced from 472.4 μm to 192.6 μm, and the maximum no-seizure load can reach 720N, which is 45.5% higher than the lubricating oil without adding extreme pressure anti-wear agent.

[0078] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that, compared with the traditional layered molybdenum oxide, the extreme pressure anti-wear agent provided by the present invention further improves the anti-wear and friction-reducing effect and extreme pressure performance of the lubricating oil.

[0079] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that the sulfurization treatment with sublimated sulfur helps to improve the anti-wear and friction-reducing effect of the lubricating oil, especially the extreme pressure performance.

[0080] It can be seen from the data of Example 2 and Comparative Examples 3-4 in Table 1 that dodecylamine and cerium can synergistically improve the anti-wear and friction-reducing effect and extreme pressure performance of lubricating oil. This is mainly because the metal ion micelles formed by dodecylamine and cerium can be intercalated and adsorbed on the inner and outer surfaces of layered molybdenum oxide, and cerium-doped carbon particles are formed after hydrothermal treatment, which improves the adsorption of layered molybdenum oxide on the friction surface and the slip between layers.

[0081] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. An anti-wear and friction-reducing composite lubricating oil, characterized in that: The invention is prepared from the following raw materials by weight: 60-80 parts of base oil, 2-4 parts of extreme pressure anti-wear agent, 0.5-1 parts of preservative, 1-3 parts of antioxidant, 1-3 parts of viscosity index improver and 1-2 parts of dispersant; The preparation method of the extreme pressure anti-wear agent is as follows: (1) adding dodecylamine to a mixed solution of deionized water and ethanol, stirring for 10-30 minutes, then adding cerium nitrate hexahydrate and layered molybdenum oxide, continuing to stir for 20-40 minutes, then hydrothermally reacting at 230-250° C. for 20-28 hours, washing, and drying to obtain a modified layered molybdenum oxide; (2) mixing the modified layered molybdenum oxide and sublimed sulfur, ball milling for 1-3 hours to obtain a mixture, heating the mixture from room temperature to 750-850° C. at 1-10° C. / min under an argon atmosphere, calcining the mixture for 2-4 hours, cooling the mixture, and grinding the mixture to obtain an extreme pressure anti-wear agent; In the step (1), the weight ratio of dodecylamine, deionized water, ethanol, cerium nitrate hexahydrate and layered molybdenum oxide is 9-24:400-600:70-130:2-6:5-15; In the step (2), the weight ratio of the modified layered molybdenum oxide to the sublimated sulfur is 1:1.5-3.

2. The anti-wear and friction-reducing composite lubricating oil according to claim 1, characterized in that: The base oil is a mixture of polyalphaolefin PAO4 and polyalphaolefin PAO6 in a weight ratio of 5:1-3.

3. The anti-wear and friction-reducing composite lubricating oil according to claim 1, characterized in that: The preservative is benzotriazole.

4. The anti-wear and friction-reducing composite lubricating oil according to claim 1, characterized in that: The antioxidant is a phenolic antioxidant.

5. The anti-wear and friction-reducing composite lubricating oil according to claim 1, characterized in that: The viscosity index improver is polymethacrylate or ethylene propylene copolymer.

6. The anti-wear and friction-reducing composite lubricating oil according to claim 1, characterized in that: The dispersant is polyisobutylene succinimide.

7. The anti-wear and friction-reducing composite lubricating oil according to claim 1, characterized in that: The preparation method of the layered molybdenum oxide is as follows: sodium molybdate dihydrate and sodium chloride are added to deionized water, stirred for 20-40 minutes, then the pH is adjusted to 2-3 with a hydrochloric acid aqueous solution, hydrothermally reacted at 170-190° C. for 20-28 hours, naturally cooled to room temperature, washed, and dried to obtain the layered molybdenum oxide.

8. The anti-wear and friction-reducing composite lubricating oil according to claim 7, characterized in that: The weight ratio of the sodium molybdate dihydrate, sodium chloride and deionized water is 9-27:4-15:300-700.

9. The anti-wear and friction-reducing composite lubricating oil according to claim 7, characterized in that: The concentration of the hydrochloric acid aqueous solution is 1-5 mol / L.

10. A method for preparing the anti-wear and friction-reducing composite lubricating oil according to any one of claims 1 to 9, characterized in that: The following steps are involved: The base oil is heated to 150°C, and then an extreme pressure anti-wear agent, a preservative, an antioxidant, a viscosity index improver and a dispersant are added, stirred for 20-40 minutes, and cooled to obtain an anti-wear and friction-reducing composite lubricant.

Citation Information

Patent Citations

  • High-temperature-resistant corrosion-resistant pressure-resistant self-lubricating chemical complex liquid and preparation and plating method thereof

    CN102409321A

  • Preparation method and application for nitrogen dioxide gas sensor based on titanium-dioxide-based porous nanocomposite

    CN105628745A

  • Anti-wearing extreme-pressure-resistant engine lubricating oil

    CN106467839A

  • Rare earth yttrium doped molybdenum disulfide self-lubricating composite coating and preparation method thereof

    CN108149220A

  • Preparation method of spherical N-doped C-coated metal oxide negative electrode material with multi-stage structure

    CN108258223A

Cited By

  • Anti-attrition lubricating oil suitable for minimal quantity lubrication and preparation method of anti-attrition lubricating oil

    CN120272261A

  • A friction-reducing lubricating oil suitable for minimal lubrication and preparation method thereof

    CN120272261B